Cascaded incremental nonlinear dynamic inversion for MAV disturbance rejection. (April 2018) - Smeur, E.J.J.; de Croon, G.C.H.E.; Chu, Q.
Abstract: This paper presents the cascaded integration of Incremental Nonlinear Dynamic Inversion (INDI) for attitude control and INDI for position control of micro air vehicles. Significant improvements over a traditional Proportional Integral Derivative (PID) controller are demonstrated in an experiment where the quadrotor flies in and out of a 10 m/s windtunnel exhaust. The control method does not rely on frequent position updates, as is demonstrated in an outside experiment using a standard GPS module. Finally, we investigate the effect of using a linearization to calculate thrust vector increments, compared to a nonlinear calculation. Highlights: A cascaded INDI attitude and position controller for quadrocopters is proposed. The controller outperforms a PID controller in terms of disturbance rejection. The controller does not rely on frequent position updates.